Aftermath of Cultural Heritage Disasters. Issue 1 (1st July 2019) - Hoffman, Sheila K.; Poulot, Dominique; Brulon-Soares, Bruno; Cobley, Joanna
Abstract : There is no doubt that we live in fraught times. In the world of museums and cultural heritage protection, we feel it keenly. As symbols and microcosms of respective cultures, museums are thought to reflect society or, at the very least, sections of society or certain historical moments. But the extent to which museums should and do reflect the diversity of people in those societies is the question du jour. Sometimes, it seems as if this question is an internal one—the practical struggle of often underfunded institutions to square the injustices of a past that is encoded into collections with a newfound awareness of visitors, or the theoretical debate about just how multivocal, democratic, and oriented toward social justice a museum can be before it ceases to be a "museum." The consequences of such struggles and debates can often seem far removed from the concerns of ordinary residents, who may only occasionally visit museums or heritage monuments. Our perception of this disregard perhaps calls into question the impact of our work. But in times of crisis, that doubt is removed and the relevance of cultural heritage becomes clear. Crisis often crystallizes what is most important. That is not surprising. In this special section, we explore the sometimes surprising nature of the aftermath.